An appraisal of the perspectives of the pentecostal and charismatic on theological education in Nigeria (2014)
This paper aims primarily at investigating the bases for the unfriendly attitude towards theological education. In addition, using historical antecedents as a benchmark, the paper will articulate the relevance of theological education in the expansion of God’s kingdom, with a view to reducing mediocrity in religious parlance and inculcate proper orientation in the development of church leaders in Nigeria. Though theological education remains a veritable platform to bring enlightenment to the souls and minds of individuals about God and his activities for the singular purpose of transforming and liberating men from the bondage of ignorance to knowledge; yet, a cursory look at the happenings among the Pentecostal and Charismatic circles in Nigeria suggests that majority of them have developed apathy towards such training. Even the few who have Bible Colleges de-emphasize rigorous theological study in their curricula, hinging such stand on many factors and assumptions.